Steve Jobs : the man who thought different : a biography - Blumenthal, Karen
Summary: Traces the inspiring life and career of the late founder of Apple, covering topics ranging from his struggles as an adopted child and a college dropout to his Buddhist faith and friendship with Steve Wozniak, in a portrait framed around his inspirational Stanford University commencement speech.